(untitled) (Research, Society and Development, 2021)
The three-dimensional creation process or additive manufacturing has a great future in medicine. Applying successive layers produces objects with incredible precision in relation to the real part. The creation of 3D models enables a more effective visualization of anatomical structures, facilitating teaching-learning, preoperative study of complex surgeries and even medical practice with the improvement of clinical technique. The present work demonstrates the feasibility of rapid prototyping or 3D digital printing in the teaching-learning process in the field of human anatomy, extending between the fields of clinical cases, surgical planning, and surgical techniques. This is a descriptive study, based on an integrative literature review, with searches in the PubMed, LILACS, SciELO and Academic Google databases, using the descriptors “Tridimensional Printing”, “Anatomy”, “Medical Education”. Many studies show clear benefits in the teaching-learning process in anatomy using 3D models produced with lower cost and great precision. In addition to the applicability in the academic and professional environment, there are still challenges to be faced, such as the cost of printers and training for their use. In this sense, the applicability of this technology has a promising future not only in medicine that involve both the basic field of knowledge and problem solving, improving the efficiency of professionals both in planning and in surgical practice.